1987
DOI: 10.1152/ajprenal.1987.252.2.f246
|View full text |Cite
|
Sign up to set email alerts
|

Direct toxic effect of the radiocontrast agent diatrizoate on renal proximal tubule cells

Abstract: The pathophysiology of radiocontrast agent-induced acute renal failure is presently unclear. To test for a possible direct deleterious effect of diatrizoate, a commonly used radiocontrast agent, on renal tubule cells, suspensions enriched in rabbit proximal tubule segments were incubated with sodium diatrizoate. After these manipulations, a variety of well-established metabolic parameters to quantitate the extent of cell injury were measured. Diatrizoate sodium (25 mM) produced significant declines in tubule K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 0 publications
5
71
0
4
Order By: Relevance
“…Filiopoulos et al reported that NGAL level at the 6 th hour had a sensitivity and specificity of 100% [16]. Plasma NGAL has been reported to be a highly specific and objective marker for the diagnosis of ARF [17][18][19]. In the current study, NGAL had an AUC level of 0.98, a sensitivity of 100% and a specificity of 95%.…”
Section: Discussionsupporting
confidence: 58%
“…Filiopoulos et al reported that NGAL level at the 6 th hour had a sensitivity and specificity of 100% [16]. Plasma NGAL has been reported to be a highly specific and objective marker for the diagnosis of ARF [17][18][19]. In the current study, NGAL had an AUC level of 0.98, a sensitivity of 100% and a specificity of 95%.…”
Section: Discussionsupporting
confidence: 58%
“…In vitr o and animal studies sug g est that damag e secondary to iodinated contrast to the kidneys is likely mediated by a combination of toxic or obstructive injury to the renal tubules, ischemic injury by reactive oxygen species, and renal medullary hypoxia. The predominant factor is likely to be renal medullary hypoxia, in which adenosine, calcium, and endothelin bring about intrarenal vasoconstriction after contrast exposure [17,[20][21][22][23][24][25] . Tubular toxicity is also thought to play a role in CIN through both direct nephrotoxicity and tubular obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ACS undergoing an emergent coronary intervention there are two well-known reasons for developing acute renal impairment. The first one is the direct toxicity of contrast medium [13] and the second one is the frequent systemic hemodynamic alteration, like blood pressure irregularities and a reduced systemic perfusion pressure in acute cardiac events [35]. The direct toxicity seems to be worse in patients with pre-existing renal insufficiency, diabetes mellitus, and atherosclerosis.…”
Section: Differences In Stemi and Nstemimentioning
confidence: 99%